PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP KELAS VII PADA MATERI PERTIDAKSAMAAN LINEAR SATU VARIABEL - Kalvia Shania Ramadhania; Nelly Fitriani; Puji Nurfauziah; M. Afrilianto (IKIP Siliwangi, 2022)
The purpose of the study was to analyze and determine the effect of the problem based learning model on the mathematical understanding ability of junior high school students on the material of one variable linear inequalities. This research is a classroom action research, which was carried out for 2 cycles. The subjects in this study were students of class VII-I of SMP Negeri 1 Cipatat in the academic year 2021/2022 with a total of 16 students. The test instrument used in the form of a description of the problem using indicators of mathematical understanding ability as many as 4 numbers on the material of one variable linear inequalities. How to process the data in the study obtained from normalized gain data, with the results of student answers in this study a score of 0.60. This shows that the students' mathematical understanding ability is increasing, with a moderate category. The non-test instrument used in the form of a scale questionnaire of students' interest in learning mathematics as many as 14 statement items containing balanced positive and negative statements. The result of the response of students' interest in learning mathematics has a strong influence on the achievement of students' mathematical understanding, which is 76.3 with a strong category.